Mobilising Voluntary Action in the UK Learning from the Pandemic - hardill, irene; Grotz, Jurgen; Crawford, Laura (Policy Press, 2022)
EPDF and EPUB available Open Access under CC-BY licence. The COVID-19 pandemic transformed the landscape of voluntary action. Some volunteering projects had to be paused, while others were delivered in different ways, but across all four UK nations large numbers of people began volunteering for the first time. This book provides an overview of the constraints and opportunities of mobilising voluntary action across the four UK nations during the pandemic. Sector experts and academics examine the divergent voluntary action policy frameworks adopted, the state and non-state supported volunteer responses, the changes in the profile of volunteers and the plans to sustain their involvement. This book addresses the urgent policy and practice need for evidence-based considerations to support recovery from the pandemic and to prepare for future emergencies.